Analisis Kemampuan Pemecahan Masalah Pada Materi Barisan dan Deret Kelas XI SMA - Alviani Milenia Safitri; Muhamad Sofian Hadi (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
Mathematics is a very important lesson that is used in various aspects of life. NCTM math learning improves communication, problem-solving, relationships, and positive attitudes toward mathematics. Polya says problem solving consists of four stages: understanding problems, planning solutions, implementing plans, and producing results. The study investigated the ability of eleventh-grade students to solve problems with row and row material using Polya indicators. The study involved twenty students from UT Karya Dharma High School and used qualitative methods. The results of the analysis show that the problem-solving process is influenced by inexperience in understanding the problem. Students who understand the problem well tend to make mistakes in the application and evaluation formula, while students who lack understanding the problem solve through the stages correctly. Ineffective solutions arise from a less thorough understanding of the problem. It shows how important it is to understand the problem accurately before proceeding to the solution stage.